1996
DOI: 10.1103/physrevd.54.3869
|View full text |Cite
|
Sign up to set email alerts
|

One-loop divergences in simple supergravity: Boundary effects

Abstract: This paper studies the semiclassical approximation of simple supergravity in Riemannian four-manifolds with a boundary, within the framework of -function regularization. The massless nature of gravitinos, jointly with the presence of a boundary and a local description in terms of potentials for spin 3/2, force the background to be totally flat. First, nonlocal boundary conditions of the spectral type are imposed on spin-3/2 potentials, jointly with boundary conditions on metric perturbations which are complete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
38
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 65 publications
(216 reference statements)
3
38
0
Order By: Relevance
“…By contrast, when the mixed boundary conditions (19)-(23) motivated by local supersymmetry are imposed, the contributions of gauge and ghost modes do not cancel each other. Both sets of boundary conditions lead to a non-vanishing ζ(0) value, and spectral boundary conditions have also been studied when two concentric three-sphere boundaries occur [2,3]. These results seem to point out that simple supergravity is not even one-loop finite in the presence of boundaries, apart from the case of those particular backgrounds bounded by two surfaces where pure gravity alone is one-loop finite.…”
mentioning
confidence: 77%
See 4 more Smart Citations
“…By contrast, when the mixed boundary conditions (19)-(23) motivated by local supersymmetry are imposed, the contributions of gauge and ghost modes do not cancel each other. Both sets of boundary conditions lead to a non-vanishing ζ(0) value, and spectral boundary conditions have also been studied when two concentric three-sphere boundaries occur [2,3]. These results seem to point out that simple supergravity is not even one-loop finite in the presence of boundaries, apart from the case of those particular backgrounds bounded by two surfaces where pure gravity alone is one-loop finite.…”
mentioning
confidence: 77%
“…The work of the authors [2,3] has found that, in the case of non-local boundary conditions (10) and (11) in the axial gauge, the contributions of ghost and gauge modes vanish separately, and hence contributions to the one-loop wave function of the universe reduce to those ζ(0) values resulting from transversetraceless perturbations only. By contrast, when the mixed boundary conditions (19)-(23) motivated by local supersymmetry are imposed, the contributions of gauge and ghost modes do not cancel each other.…”
mentioning
confidence: 99%
See 3 more Smart Citations